SIMURG: A new model for the integrated assessment of sustainability - Kanoglu, Alaattin; Yazicioglu, Deniz; Ozcevik, Ozlem; Erkovan, Nisa; Softaoglu, Hidayet; Ulker, Burcu; Varlier, Nazli; Yazicioglu, Ediz (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
Sustainability assessment is one of the basic issues in the agenda of public authorities and it requires practical tools to measure performance in terms of sustainable development goals. Most studies in literature deal with only one dimension of the problem of environmental components of sustainability. These studies discuss entities at only one level (cities, buildings, etc.), and one layer (green, smart, etc.) in selected dimensions. The literature includes no models that claim to provide an integrated assessment of entities’ performance in the 3D Cartesian system. The presently available models do not offer solutions that would be applicable in practice. SIMURG (A performance-based and Sustainability-Oriented Integration Model Using Relational database architecture to increase Global competitiveness of construction industry) proposes using layers and their KPI sets in the assessment process. In addition to philosophical, organisational, integrational, and computational models, this study aims to develop a lean architecture of a relational database model by eliminating ineffective solutions in the practical dimension, i.e. in the computer model. The model can be used by individuals to help them choose built environment whose characteristics match their expectations. Public authorities can utilise the model to increase the level of accountability, transparency, and legitimacy in their decision-making processes.